Mechanical and flexural behaviour study on fibrillated concrete as partial replacement of M-Sand and metakaolin. (2021) - Abiraami, R.; Anuradha, R.; Johnpaul, V.; Guruprasad, M.; Gobinath, R.; Sivakrishna, A.; Shrihari, S.
Abstract: Generally, the fine aggregate of the concrete mix facilitates a huge workable one. Currently, there is a demand in river sand supply to undertake construction work. Compared to the river sand, M-Sand works as an eco-friendly resource. Metakaolin, introduced to increase the compression and the bending nature of concrete. Steel fibre is used to measure the ductility of the concrete. The experimental work carried out by preparing five concrete mixtures varying 10% of M-Sand ranging 60–100 percent by weight of fine aggregate, 15% by weight of cement, and 1% by volume of steel fibre; the fraction kept constant based on previous studies. Various proportions of M30grade concrete were examined by conducting mechanical and flexural behaviour tests. The results obtained are satisfactory for 80% of the M-Sand replacement. Additional M-Sand replacement tends to reduce concrete strength.